Effect of Slag on Restoration Mechanical Characteristics of Ethanol Gasoline-Contaminated Clay - Keramatikerman, M.; Chegenizadeh, Amin; Nikraz, Hamid (2018)
This study investigates the effect of slag on the mechanical characteristics of clay contaminated with ethanol gasoline (E10) by performing a series of unconfined compressive strength (UCS) tests. The effect of slag in four percentages of 0, 2, 4, and 6% (by dry weight) and three curing periods of 7, 14, and 28 days on clay contaminated with different E10 contents (i.e., 0, 3, 5, and 7% by dry weight) was examined. Additionally, 1% portland cement (PC) was added into all of the mixtures to keep the integrity of the untreated specimens and for ease of comparison. The compaction test results showed that the addition of E10 reduced the optimum moisture content (wopt) and increased the maximum dry density (?dmax), but that the addition of slag caused adverse behavior for the mentioned parameters. The analysis of the UCS results showed that increasing E10 reduced the peak UCS (qu) values, but that the addition of slag and curing time was effective in improving the peak UCS values. The presence of oriented soil particles in a contaminated specimen was observed through scanning electron microscopy (SEM) analysis. The reduction of peak UCS values was confirmed to be due to the sliding behavior of soil particles induced by the viscose nature of E10. Additionally, observing a lower peak intensity value in the X-ray powder diffraction (XRD) pattern of the hydration products was another reason for recorded lower peak UCS values in contaminated specimens.